ESP32-Based Smart Office Prototype with Wi-Fi and MQTT Integration on Telecommunications Infrastructure: Telekomunikasi Militer - Rifqi Susendo; Isa Mahfudi; Agung Wibowo (Pustaka Poltekad, 2025)
Abstract:The development of the Internet of Things (IoT) has encouraged the adoption of smart office concepts to improve operational efficiency. This study presents a smart office prototype based on the ESP32 microcontroller, integrated with Wi-Fi connectivity and the MQTT communication protocol. The system is designed to monitor environmental conditions, such as temperature and humidity, while enabling real-time control of electronic devices through a Node-RED dashboard. System evaluation was conducted by measuring communication latency, sensor accuracy, power consumption, network stability, and data security. The results indicate low latency, reliable sensor accuracy, and support for multi-user access without performance degradation. In addition, the system implements Transport Layer Security (TLS) encryption to protect data from potential cyber threats. With its low implementation cost and high integration flexibility, the prototype is considered feasible for broader operational deployment, particularly in office telecommunication environments that demand automation, energy efficiency, and productivity improvement. Keywords: Smart Office, ESP32, Wi-Fi, MQTT, Internet of Things, Office Automation, Node-RED, Energy Efficiency